Extent of Knowledge of Vegetable Growers about the Side Effects of Pesticides (Indian Journal of Extension Education, 2010)
Vegetables being a rich and cheap source of vitamins, minerals and antioxidants, occupy an important place in the food basket of Indian consumers. A majority of people are vegetarian either by choice or due to lack of access. The study was conducted in Varanasi district of Uttar Pradesh. The respondents were selected from the five villages of Araziline block for the study purpose. The total number of respondents was 208, randomly selected from each village. An index was developed for studying the knowledge about the side effects of pesticides. The data were collected and classified into three categories namely low, medium and high levels based on the mean and standard deviation. The findings revealed that the knowledge level of respondents about the side effects of pesticides was low. It is evident from the study that the education and communication behaviour of farmers are to be taken into consideration with full certainty in making sound strategies of development plan. If farmers become more aware of the judicious use of pesticides it will reduce the hazards related to unjudicious pesticide use.